Treaty shopping in international investment law - Baumgartner, Jorun (Oxford : Oxford University Press, 2017)
Analysing how arbitral tribunals have dealt with the value judgment at the core of the distinction between 'objectionable' and 'unobjectionable' treaty shopping, this book suggests how States could reform their international investment agreements in order to make them less susceptible to the practice of treaty shopping.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 7, 2016).
Keywords: Investments, Foreign (International law); Double taxation; Law; Laws of specific jurisdictions & specific areas of law